Mesenteric Schwannoma, Intestinal Malrotation and Ileal Diverticulum: A Unique Association - Alberto Abreu da Silva; Andreia Ferreira; Pierpaolo Cusati; José Augusto Martins (Acta Médica Portuguesa, 2022)
Mesenteric schwannomas are rare benign tumors that arise in the mesentery. Ileal diverticula and intestinal malrotation in adults are rare findings, since they are usually asymptomatic. We present the case of an 86-year-old man, without any known previously known medical conditions, who was admitted in the emergency department with recurrent abdominal distension and intense pain. The radiological study suggested an intestinal malrotation. An exploratory laparotomy confirmed the intestinal malrotation with intermesenteric bands, as well as a mesenteric mass adjacent to an ileal diverticulum. Following a segmental enterectomy, the histology of the mass reported a mesenteric schwannoma. To the best of our knowledge, this is the first report of such association. We therefore present this report to showcase the diagnostic and therapeutical challenges in managing these conditions.